Inovasi Dalam Kejuruteraan Mekatronik : Perbandingan Pencapaian Pelajar Yang Berorentasikan Kemahiran Analisis Dengan Berorentasikan Sosial - Razali, Zol Bahri (Journal of Techno-Social, 2009)
Conventional ways of teaching Mechanical or Mechatronics Engineering subjects are no longer relevant. With the expending of latest technology, students need to be exposed with real-life apparatus to increase the awareness and understand more on the engineering concepts. Nevertheless, the lacking of these equipments, partly due to its size, cost and space, has hardened the learning process. Therefore, suitable teaching aids can be used to ensure students’ comprehension between theory and reality part. In addition, the different cognitive styleof students need different approach of learning. Multimedia-based learning modul can be performed in order to tackle the problem. Hence, this research is conducted to study and recognize the usage of learning module based on multimedia in education of Mechatronics Engineering subjects, which is focussing on students with analysis skill orientation and social orientation.The main objective of this research is to study the efficiency of multimedia learning courseware towards Mechatronics Engineering students. The aim was to identify whether there is significant difference existed in overall achievement compared to the conventional method of learning. Results obtained have proved the effectiveness of this multimedia learning modul due to the increment of score in students’ performance test to low internal motivation and dependent students.